THE «EXECUTIVE SEIZURE» IN COMPARATIVE LAW. ATTEMPT A DEFINITION APPLICABLE TO THE CHILEAN LEGAL SYSTEM - Ríos Muñoz, Luis Patricio (2017)
The concept of seizure is understood in a way by legos and another by lawyers. There are two positions: the litigators, which deliver a restricted concept that agrees with the figure of the executive seizure, and the civil, who opt for a broader concept which also reaches the measures precautionary, and among them the so-called preventive seizure. This article aims to highlight the distinction between those meanings, to review the various concepts we find in sources both legal and extra- legal and, finally, attempting a comprehensive definition of what in our national legal system should be understood by executive seizure.